Hydrochemistry of springs in the bambui-sabga volcanic area (north west region, Cameroon volcanic line) - Pierre, Wotchoko; Margaret Awah, Tita; Gus Djibril, Kouankap Nono; Magha, Alice; Lawrence Mbitegemboh, Fosap; Christian Suh, Guedjeo; Zenon, Itiga; Marie Louise Vohnyui, Chenyi; Veronique, Kamgang Kabeyene (International Journal of Advanced Geosciences, 2015)
This study was carried out in the Bambui-Sabga volcanic area in Tubah Sub-Division, North West Region, Cameroon. This research was aimed at carrying out a hydrochemical characterization of springs in the area. Chemical analysis were done using a DR 2010 Hach Spectrophotometer. The analysed spring samples were close to neutral (pH 6.9-7.6) with a high electrical conductivity ranging from 1,400 - 11,400 ÂµS/cm and TDS from 750 - 7,960 mg/l. The FS01 spring recorded the highest average temperature of 34oC, yellowish-brown in colour and rusty odour, while the FS02 spring had a salty taste and soapy feel. The FS02 spring recorded the highest Na+ concentration of 128 mg/l. The analyzed springs can be classified into: thermal spring (FS01), salt spring (FS02) and normal (mineral) spring (FS03). The spring waters showed a (Na+K)-Cl (SO4) facies and are stable with Na-montmorillonite and zeolites, with their mineralisation from evaporation, salt water intrusion and leaching. Physical parameter were enriched in the dry season except for pH, and deficient in cations and anions except NO3- in FS02. In the rainy season, chemical enrichment was higher. The spring waters were not suitable for drinking and should be treated before human consumption.